Unfulfilled promise: social acceptance of the smart grid. (17th February 2021) - Bugden, Dylan; Stedman, Richard
Abstract: Smart grids use digital information technology to simultaneously increase energy efficiency while integrating renewables into the electric grid, making it a critical component of achieving a low-carbon energy system. Prior research on the social acceptance of smart grids has relied on either single time point assessment (i.e. prior to a smart grid rollout) or experimental and lab settings. These approaches miss key aspects of social acceptance because they fail to capture change over time through the interaction between stakeholders, technology, and utilities. In contrast, we compare two waves of survey data on the social acceptance of smart grid technologies, the first ( n = 609) prior to a local rollout of a smart grid program in upstate New York and the second ( n = 533) two years after the same rollout. Our results demonstrate that in contrast to the hopes of smart energy advocates, the social acceptance of four dimensions of smart grids either remain steady or decline over time. Further analyses reveal that the factors that shape acceptance also change over time. This study demonstrates that the social acceptance of smart grids may actually decrease over time even with the robust engagement of consumers, not only challenging optimistic views of smart grid technology but also challenging broader theoretical arguments in the literature on the social acceptance of energy technologies.